2014
DOI: 10.1093/heapol/czu043
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the ability to deliver care in low- and middle-income countries: a systematic review of health facility assessment tools

Abstract: Introduction Health facilities assessments are an essential instrument for health system strengthening in low- and middle-income countries. These assessments are used to conduct health facility censuses to assess the capacity of the health system to deliver health care and to identify gaps in the coverage of health services. Despite the valuable role of these assessments, there are currently no minimum standards or frameworks for these tools.Methods We used a structured keyword search of the MEDLINE, EMBASE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Much of the data on quality in low‐ and middle‐income countries have focused on structure (e.g., medicines, equipment, staff, provider knowledge; Nickerson et al. ). Here, we examine a process measure of quality: the content of clinical care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the data on quality in low‐ and middle‐income countries have focused on structure (e.g., medicines, equipment, staff, provider knowledge; Nickerson et al. ). Here, we examine a process measure of quality: the content of clinical care.…”
Section: Methodsmentioning
confidence: 99%
“…Donabedian proposed that quality of care be assessed through structure, processes, and outcomes (Donabedian 1988). Much of the data on quality in low-and middle-income countries have focused on structure (e.g., medicines, equipment, staff, provider knowledge; Nickerson et al 2015). Here, we examine a process measure of quality: the content of clinical care.…”
Section: Methodsmentioning
confidence: 99%
“…A recent comprehensive review of health-facility assessment tools in low- and middle-income countries found that among the 10 tools that met the study´s inclusion criteria there was substantial variation in their content and comprehensiveness. Of the 41 domains for comprehensive health system measurement identified by the authors, the actual number of domains covered by each of the assessment tools ranged from 13 to 33, with a median of 25.5 40 . For example, even when data on the health workforce were available, the indicators on staff presence and availability of emergency staff were mostly missing, as were any assessments of the clinical training the staff had received 40 .…”
Section: Policy Gapsmentioning
confidence: 99%
“…Of the 41 domains for comprehensive health system measurement identified by the authors, the actual number of domains covered by each of the assessment tools ranged from 13 to 33, with a median of 25.5 40 . For example, even when data on the health workforce were available, the indicators on staff presence and availability of emergency staff were mostly missing, as were any assessments of the clinical training the staff had received 40 . The review raised two concerns; first, the data being collected at the health facility level are inconsistent, incomplete and difficult to compare; and second, there is a preference towards the evaluation of primary-care services over those of secondary and tertiary care 40 .…”
Section: Policy Gapsmentioning
confidence: 99%
See 1 more Smart Citation